The use of information technologies to predict and diagnose the psychological trauma of servicemen – combatants (Law and Safety, 2018)
Based on the analysis of existing developments in the field of automation of psychological and psycho-physiological testing procedures, as well as own empirical studies of combat psychological trauma of servicemen – combatants, the authors within the scientific research “Development of Preventive Program of Post-Trauma Stress Disorders of Servicemen of the National Guard of Ukraine”, have offered own approach to the creation of the complex of automated methods for determining resistance to psychological trauma by the combat experience, presence / absence of the features of post-traumatic stress disorder, presence / absence of psychological trauma of the combat experienceThe specified automated complex allows to get test results for each respondent in each method and to make complete characteristics of his mental health with the consequent possibility to convert textual information into a Microsoft Word document. Such a psycho-diagnostic testing document (profile) contains information about the respondent (last name, first name, middle name, group number), as well as numerous results of passing each psychological test (title, time, date, basic indicators) and their interpretation. If any test is failed, a record on its failure is made in the profile. While passing the main tests of the complex there is information in the profile about the type of psychological trauma of a person and the description.The use of the automated psycho-diagnostic complex “Combat Psychological Trauma of Individuals” improves the accuracy, efficiency and effectiveness of the psychological work of psychologists of military units of the National Guard of Ukraine in assessing the level of psychological trauma by the combat experience. The practical component of the automated psycho-diagnostic complex is the formation of recommendations based on the obtained test results, with the determination of the possibility of servicemen further engagement to participate in combat operations.
Keywords: psychological trauma; combat operations; a serviceman; National Guard of Ukraine; combat experience; adaptation; behavior; complex; database structure; algorithm